PENGARUH PEMBERIAN PROBIOTIK DENGAN DOSIS YANG BERBEDA PADA MEDIA BUDIDAYA TERHADAP PERTUMBUHAN DAN KELULUSHIDUPAN IKAN NILA (Oreochromis niloticus) - Imam Eka Apriyan; Nanda Diniarti; Bagus Dwi Hari Setyono (Jurnal Perikanan Unram, 2021)
Nile Tilapia (Oreochromis niloticus) is one type of freshwater biota that has high economic value. This study aims to evaluate the effect of adding probiotic EM4 to Nile Tilapia culture media on tilapia's growth and survival and select the best dose of adding EM4 probiotic to culture media on the growth and survival of tilapia. The tilapia used in this study was 4-5 cm in size. And the research was carried out using a completely randomized design (CRD) method with 4 treatments and 3 replications so that 12 experimental units were obtained; the treatments were as follows: P1 = Without Addition of Probiotics (Control), P2 = Addition of Probiotics 0.5 ml/l of water, P3 = Addition of Probiotics 1.5 ml/l of water and P4 = Addition of Probiotics of 2.5 ml/l of water. The data obtained were then processed and calculated using analysis of variance (ANOVA) at a 95% confidence interval if a significant effect was found, then continued with Duncan's further test. This study indicates that the addition of probiotic EM4 to tilapia culture media can affect the growth of absolute weight, SGR, FCR, and survival rate of Nile Tilapia. The addition of probiotics in the P3 treatment (Addition of Probiotics 1.5 ml/l water) gave the best effect in increasing the growth and survival of Nile Tilapia (Oreochromis niloticus).